Mechanization in potato cultivation - Nare, Brajesh; Singh, Sukhwinder (Indian Horticulture, 2020)
Potato is a crop with huge output per unit area. Production, handling and processing of potato takes lot of time and energy if all the operations are completed manually or with the help of animal drawn equipments. A number of efficient farm machineries and equipments are available in India to carry out timely field operations like seedbed preparation, fertilizer application, planting, weeding, earthing, digging, grading and seed treatment. Therefore, in this era of competitive agriculture, for efficient use of expensive inputs like seeds and fertilizers, farmers should opt for precise application of the farm inputs through mechanization and should use potato planters, fertilizer applicators, weeders, diggers, graders and other available machines. Some of these machines are expensive and are not in the reach of small farmers. In cases such group of farmers can purchase the machine or an individual farmer can have it and go for custom hiring for more returns. Similarly, cooperatives can be useful for having processing machineries at village or cluster levels.